2013
DOI: 10.1002/hep.26314
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of large spontaneous portosystemic shunts for refractory hepatic encephalopathy: A multicenter survey on safety and efficacy

Abstract: Refractory hepatic encephalopathy (HE) remains a major cause of morbidity in cirrhosis patients. Large spontaneous portosystemic shunts (SPSSs) have been previously suggested to sustain HE in these patients. We aimed to retrospectively assess the efficacy and safety of patients treated with embolization of large SPSSs for the treatment of chronic therapy-refractory HE in a European multicentric working group and to identify patients who may benefit from this procedure. Between July 1998 and January 2012, 37 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
222
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 33 publications
2
222
0
4
Order By: Relevance
“…However, in a large multicentre European cohort study, Laleman et al found that there was no significant increase in de novo development or aggravation of preexisting varices, portal hypertensive gastropathy, or ascites. 6 This study showed overall improvement in autonomy, decreased number of hospitalizations and, and severity of the worst HE episode in threequarters of the patients. Partial splenic embolisation has been suggested as additional treatment by some authors.…”
Section: Discussionmentioning
confidence: 54%
“…However, in a large multicentre European cohort study, Laleman et al found that there was no significant increase in de novo development or aggravation of preexisting varices, portal hypertensive gastropathy, or ascites. 6 This study showed overall improvement in autonomy, decreased number of hospitalizations and, and severity of the worst HE episode in threequarters of the patients. Partial splenic embolisation has been suggested as additional treatment by some authors.…”
Section: Discussionmentioning
confidence: 54%
“…Critical point drying or HMDS (hexamethyldisilazane) drying can be applied after dehydration for scanning electron microscopy (SEM). 1 Jet-fixation leads to well-fixed tissue with open sinusoids, free of blood cells (Fig. 2B,C).…”
Section: Jet-fixation: a Novel Methods To Improve Microscopy Of Human mentioning
confidence: 95%
“…Transmission electron microscopy (TEM) has contributed considerably to liver research [1][2][3][4][5][6][7][8][9][10] after the introduction of perfusion fixation, with glutaraldehyde fixative through the portal vein. A clear distinction of sinusoidal endothelial, Kupffer, pit, and stellate cells became apparent, including details such as the endothelial fenestrae.…”
Section: Jet-fixation: a Novel Methods To Improve Microscopy Of Human mentioning
confidence: 99%
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%